Measuring Students’ Use of Zoom Application in Language Course Based on the Technology Acceptance Model (TAM) - Alfadda, Hind Abdulaziz; Mahdi, Hassan Saleh (Journal of psycholinguistic research, 2021)
The study uses technology acceptance model (TAM) to gain insights into user reactions to the technology adopted for language learning. The study aims to analyze the correlation between the variables of TAM on using Zoom application in language learning, in addition to examining how gender and experience influence the use of technology. The participants of this study comprise of 75 undergraduate English-as-Foreign-Language learners who have studied for their courses online during the COVID-19 pandemic. The results of the study reveal a strong positive correlation between the actual use of Zoom and the students’ attitudes and behavioral intention. In addition, there is a positive correlation between computer self-efficacy and other variables (i.e. PU, actual use, PEU, attitude and behavioral intention). Further, while the results reveal that there is no correlation between the gender and any variables of the model, it has been found that experience is positively correlated with the variables of TAM.